New journal for rural development practitioners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Rural Development in Practice which came out for the first time in August 1988, is a quarterly international journal for rural development practitioners